2012
DOI: 10.1111/j.1756-1051.2012.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Livestock grazing ingestion suppressed the dominant species population (Stipa aliena) germination: a laboratory experiment

Abstract: Grazing has an important effect on population dynamics in grassland vegetation. This paper aims at providing information on the impact of livestock ingestion on seed germination in a Tibetan meadow. We conducted a laboratory germination experiment in which Stipa aliena seeds were treated by yak and Tibetan sheep rumen fluids and yak dung extract with undiluted, 1-fold and 10-fold diluted solutions. The results showed that seed germinability was restrained in all these treatments. In the control treatment, 66.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several authors found in similar experiments that the seeds of Stipa aliena [30], Saussurea japonica and Saussurea iodostegia [31] and Vicia angustifolia [29] exposed to microbial digestion in the rumen did not germinate or that seed germination was significantly reduced, whereas in the present experiment, only the germination of R. obtusifolius was studied. Even if the rumen juice in the present Experiment I had a stimulating effect on seed germination (the microbes thin the cell wall of the seeds with their microbial activity and thus accelerate germination), the discrepancies between the studies are most likely due to the fact that different plant species react differently to microbial digestion.…”
Section: Experiments I: Seed Viability After Ensiling and In Vitro Di...mentioning
confidence: 56%
See 1 more Smart Citation
“…Several authors found in similar experiments that the seeds of Stipa aliena [30], Saussurea japonica and Saussurea iodostegia [31] and Vicia angustifolia [29] exposed to microbial digestion in the rumen did not germinate or that seed germination was significantly reduced, whereas in the present experiment, only the germination of R. obtusifolius was studied. Even if the rumen juice in the present Experiment I had a stimulating effect on seed germination (the microbes thin the cell wall of the seeds with their microbial activity and thus accelerate germination), the discrepancies between the studies are most likely due to the fact that different plant species react differently to microbial digestion.…”
Section: Experiments I: Seed Viability After Ensiling and In Vitro Di...mentioning
confidence: 56%
“…This value is statistically the lowest compared to the other germination energies achieved by R. obtusifolius. Similarly, many studies [29,30] have confirmed that the seed germination capacity generally decreases with the time spent in the digestive tract and that microorganisms in the rumen significantly reduce seed germination.…”
Section: Experiments I: Seed Viability After Ensiling and In Vitro Di...mentioning
confidence: 82%